Supplement for sanitary ceramic dry body and preparation method thereof

By using clinker powder, silicon powder and other raw materials in the dry blank supplement for sanitary ceramics, the problems of shrinkage and repairing areas falling off during firing of sanitary ceramics are solved, and the bonding strength between the repairing areas and the dry blank is improved, ensuring high-quality output.

CN119874328AActive Publication Date: 2025-04-25TANGSHAN RENAULT PORCELAIN CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510019951.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-04-25
Estimated Expiration
2045-01-07

AI Technical Summary

Technical Problem

During the production process of sanitary ceramics, the plastic clay in the blank causes the blank to shrink during firing, which may cause cracks and repairs to fall off, affecting the production of high-quality products.

Method used

It provides a supplement for dry sanitary ceramics, containing clinker powder, silicon powder, blank, glaze slurry, sodium carboxymethylcellulose solution and medium temperature fuse powder. Through the combination of these raw materials, the refractory resistance and binding strength of the supplement are improved, and the possibility of scaling shrinkage and shedding is reduced.

Benefits of technology

By improving the refractory resistance and bonding strength of the supplement, the possibility of cracking or falling off of the dry blank repairing place during the secondary firing process is reduced, the bonding strength between the repairing place and the dry blank is improved, and the adverse impact on the yield of the blank is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to the technical field of sanitary ceramic preparation, and particularly discloses a supplement for a sanitary ceramic dry body and a preparation method of the supplement. The supplement for the sanitary ceramic dry body comprises clinker powder, silica powder, a blank, glaze slip, a sodium carboxymethyl cellulose solution and medium-temperature frit powder. The preparation method comprises the following steps: adding the glaze slip and the blank into a sodium carboxymethyl cellulose solution, uniformly mixing, adding the clinker powder, the silica powder and the medium-temperature frit powder into the prepared slurry, and uniformly mixing. The repairing agent for the sanitary ceramic dry body can be used for repairing the sanitary ceramic dry body with cracks and other defects, and has the advantage of reducing the adverse effect on the yield of a fine body product.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of sanitary ceramic preparation, and more specifically, to a supplement for sanitary ceramic dry blanks and a preparation method thereof. Background Art

[0002] The molding of sanitary ceramics is mainly based on the plasticity of the blank, so that the blank is made into a blank of various shapes, and the blank is dried and fired to produce the finished sanitary ceramics. During the ceramic production process, the plastic clay in the blank is easy to cause the blank to shrink during firing, resulting in defects such as cracks in the blank.

[0003] In order to reduce the scrap rate in the production process of sanitary ceramics, the cracks on the green body are usually repaired with green body, and the repaired green body is fired for the second time to dry the repaired part. At this time, since the green body contains plastic clay and has not been fired, it is easy to cause the repaired part of the green body to fall off during the second firing of the green body, which will have an adverse effect on the production of high-quality green body. Summary of the invention

[0004] In order to reduce the adverse effects on the yield of high-quality green bodies, the present application provides a supplement for sanitary ceramic dry green bodies and a preparation method thereof.

[0005] In the first aspect, the present application provides a supplement for dry blanks of sanitary ceramics, which adopts the following technical solution: A supplement for dry ceramic blanks, comprising the following raw materials in parts by weight: 40-60 parts of clinker powder, 5-15 parts of silicon powder, 10-30 parts of green body, 5-15 parts of glaze slurry, 0.5-1 part of 1-2% sodium carboxymethyl cellulose solution by mass, and 4-6 parts of medium temperature frit powder.

[0006] By adopting the above technical scheme, clinker powder is added to the blank to improve the refractoriness of the filler, so that the refractoriness of the filler is higher than that of the blank; thus, some pores are generated in the filler during the secondary firing of the dry blank, thereby reducing the firing shrinkage of the filler and reducing the possibility of cracking or falling off of the filler during the secondary firing process; the silicon micropowder added to the filler produces a slight volume expansion during firing and forms a skeleton at the repaired part of the dry blank, thereby offsetting part of the firing shrinkage during the secondary firing of the filler. At this time, since the shrinkage rate of the dry blank during the secondary firing process is greater than the shrinkage rate of the filler, compressive stress is generated at the repaired part of the dry blank, thereby improving the bonding strength between the repaired part and the dry blank; the sodium carboxymethyl cellulose solution has viscosity at room temperature, thereby facilitating the bonding of the prepared filler to the cracks of the dry blank, thereby reducing the possibility of the repaired part detaching from the dry blank at room temperature; The glaze slurry and medium-temperature frit powder further increase the viscosity of the filler during the secondary firing of the dry blank, thereby facilitating the improvement of the bonding strength between the filler and the dry blank at high temperature, further reducing the possibility of the repaired part being separated from the dry blank after the secondary firing is completed, facilitating the repair of cracked dry blanks, and reducing the adverse effects on the production of high-quality blanks.

[0007] Preferably, the particle size of the silicon micropowder is 100±10 mesh, and the particle size of the medium-temperature frit powder is 200±10 mesh.

[0008] By adopting the above technical scheme, the silicon micropowder and medium-temperature frit powder of the above-mentioned particle size are selected and mixed with other raw materials to prepare a supplement. At this time, the silicon micropowder and the medium-temperature frit powder form a structural skeleton in the prepared supplement, and at the same time make the powder materials in the prepared supplement more tightly combined, further reducing the possibility of sintering shrinkage of the supplement; when the particle size of the silicon micropowder and the medium-temperature frit powder is greater than the above-mentioned value, it is easy to cause the particle size of the silicon micropowder and the medium-temperature frit powder to be too large, making it difficult for the powder materials in the raw materials to form a stable particle grading, thereby adversely affecting the bonding tightness; when the particle size of the silicon micropowder and the medium-temperature frit powder is less than the above-mentioned value, it is easy to cause the separation agglomeration and it is difficult to be evenly distributed in the supplement, thereby affecting the compactness of the powder particles.

[0009] Preferably, the clinker powder is prepared by mixing waste porcelain powder and burnt bauxite in a weight ratio of (6-10):2.

[0010] By adopting the above technical scheme, waste porcelain powder and burned bauxite are mixed to prepare clinker powder, so that waste porcelain materials can be reused and the refractoriness of the filler is made higher than that of the dry blank. As a result, during the secondary firing, the filler forms internal pores due to incomplete firing, which reduces the firing shrinkage of the repaired part of the dry blank, thereby reducing the possibility of cracking or falling off of the repaired part of the dry blank, and reducing the adverse effects on the output of high-quality blanks.

[0011] Preferably, the waste porcelain powder is prepared by mixing 60±10 mesh waste porcelain powder and 100±10 mesh waste porcelain powder in a weight ratio of (1-3):1, and the burnt bauxite is prepared by mixing 60±10 mesh burnt bauxite and 100±10 mesh burnt bauxite in a weight ratio of (1-3):1.

[0012] By adopting the above technical scheme, waste porcelain powder and burned bauxite are prepared from powder particles of 60 mesh and 100 mesh, thereby forming a particle grading with other powder materials in the raw materials, and further forming a compact powder material in the supplement. At this time, the large particles in the supplement form a structural stock, and the small particles of powder fill the gaps between the large particles, reducing the possibility of shrinkage during firing of the supplement, thereby reducing the possibility of cracking or falling off at the repaired part of the dry blank.

[0013] Preferably, the raw materials also include 3-5 parts of heavy calcium carbonate powder.

[0014] By adopting the above technical solution, heavy calcium carbonate is added to the raw materials, and when the filler is used to repair the cracks on the dry blank and the blank is fired for the second time, the heavy calcium carbonate decomposes at high temperature to generate calcium oxide and carbon dioxide, thereby further forming gas in the filler and compensating for the firing shrinkage of the filler, reducing the possibility of cracking or falling off at the repaired part of the dry blank, and further reducing the adverse effects on the yield of high-quality blanks.

[0015] Preferably, the heavy calcium carbonate powder is a modified heavy calcium carbonate powder, and the modified heavy calcium carbonate powder is prepared from zinc stearate and heavy calcium carbonate in a weight ratio of (1-2): 100, and the modified heavy calcium carbonate powder is prepared by the following steps: The heavy calcium carbonate powder is stirred in a water bath at 60-80° C. at a speed of 600-800 r / min, zinc stearate is added to the heavy calcium carbonate powder according to a weight ratio, mixed for 30-70 minutes, and then cooled to obtain a modified heavy calcium carbonate powder.

[0016] By adopting the above technical scheme, zinc stearate is connected to heavy calcium carbonate in the form of a chemical bond to obtain modified heavy calcium carbonate, without changing the crystal structure of heavy calcium carbonate, and improving the dispersibility of heavy calcium carbonate, so that the heavy calcium carbonate is evenly distributed in the supplement. When the supplement is prepared, the zinc stearate on the modified heavy calcium carbonate is dissolved in water. At this time, the zinc stearate further thickens the supplement, improves the adhesion of the supplement to the dry blank at room temperature, and during the secondary firing, the zinc stearate decomposes at high temperature to form zinc oxide, thereby improving the toughness and hardness of the repaired part of the dry blank, and improving the mechanical properties of the repaired part of the dry blank.

[0017] In a second aspect, the present application provides a method for preparing a supplement for a sanitary ceramic dry blank, using the following technical solution: A method for preparing a supplement for a sanitary ceramic dry blank comprises the following steps: Adding glaze slurry and blank into sodium carboxymethyl cellulose solution according to weight parts and mixing evenly to prepare slurry; The clinker powder, silicon powder and medium-temperature frit powder are added into the prepared slurry according to weight proportions and mixed evenly to prepare a supplement for dry blanks of sanitary ceramics.

[0018] By adopting the above technical scheme, after the sodium carboxymethyl cellulose solution, blank and glaze slurry are mixed to prepare slurry, the clinker powder, silicon micropowder and medium-temperature frit powder are added to the slurry and mixed evenly, which is convenient for mixing the raw materials and preparing the supplement for sanitary ceramic dry blank.

[0019] A method for preparing a supplement for a sanitary ceramic dry blank comprises the following steps: Adding glaze slurry and blank into sodium carboxymethyl cellulose solution according to weight parts and mixing evenly to prepare slurry; Mix clinker powder, silicon powder, heavy calcium carbonate and medium-temperature frit powder according to weight to obtain dry powder; The prepared dry powder is added into the prepared slurry and mixed evenly to obtain a supplement for sanitary ceramic dry blanks.

[0020] By adopting the above technical scheme, after the sodium carboxymethyl cellulose solution, the blank and the glaze slurry are mixed to obtain the slurry, the clinker powder, silicon micropowder, heavy calcium carbonate and the medium-temperature frit powder are mixed to obtain the dry powder, and the dry powder and the slurry are mixed. At this time, the heavy calcium carbonate is first mixed with other powders in the raw materials and then mixed with the slurry, so that the heavy calcium carbonate is evenly dispersed and the supplement for the dry blank of sanitary ceramics is obtained.

[0021] In summary, this application has the following beneficial effects: 1. The clinker powder makes the refractoriness of the filler higher than that of the blank, and some pores are generated in the filler during the secondary firing of the dry blank, reducing the firing shrinkage of the filler; the silicon powder expands slightly during firing and forms a skeleton at the repaired part of the dry blank, offsetting some of the firing shrinkage, so that compressive stress is generated at the repaired part of the dry blank during the secondary firing, and the bonding strength between the repaired part and the dry blank is improved; the sodium carboxymethyl cellulose solution facilitates the bonding of the filler to the cracks of the dry blank, reducing the possibility of the repaired part detaching from the dry blank at room temperature; the glaze slurry and the medium-temperature frit powder facilitate the bonding strength between the filler and the dry blank at high temperature, reducing the possibility of the repaired part detaching from the dry blank after the secondary firing is completed.

[0022] 2. Waste porcelain powder and burnt bauxite are both made of 60-mesh and 100-mesh powder particles, thus forming a particle gradation with other powders in the raw materials, and further forming a dense powder in the supplement. At this time, the large particles in the supplement form a structural stock, and the small particles of powder fill the gaps between the large particles, reducing the possibility of shrinkage during sintering of the supplement.

[0023] 3. Zinc stearate modifies heavy calcium carbonate, which improves the dispersibility of heavy calcium carbonate. When the supplement is prepared, the zinc stearate on the modified heavy calcium carbonate dissolves in water and thickens the supplement, improving the adhesion of the supplement to the dry billet at room temperature. During the secondary firing, the zinc stearate decomposes at high temperature to form zinc oxide, which improves the toughness and hardness of the dry billet repair. DETAILED DESCRIPTION

[0024] The present application is further described in detail below in conjunction with preparation examples and embodiments.

[0025] raw material All raw materials in the preparation examples and embodiments can be obtained from commercial sources. The sodium carboxymethylcellulose solution is prepared from sodium carboxymethylcellulose powder and deionized water.

[0026] Preparation Example Preparation Example 1 Clinker Powder Preparation Example 1.1 A clinker powder is prepared by the following steps: Mix 22.5 kg of 60-mesh waste porcelain powder and 22.5 kg of 100-mesh waste porcelain powder to obtain mixed waste porcelain powder; Mix 7.5 kg of 60-mesh burnt bauxite and 7.5 kg of 100-mesh burnt bauxite to obtain mixed burnt bauxite; The prepared mixed waste porcelain powder and the prepared mixed burned bauxite are mixed evenly to prepare clinker powder.

[0027] Preparation Example 1.2 Different from Preparation Example 1.1, in Preparation Example 1.2, the amount of 60-mesh waste porcelain powder added is 24 kg, the amount of 100-mesh waste porcelain powder added is 24 kg, the amount of 60-mesh burned bauxite added is 6 kg, and the amount of 100-mesh burned bauxite added is 6 kg.

[0028] Preparation Example 1.3 Different from Preparation Example 1.1, in Preparation Example 1.3, the amount of 60-mesh waste porcelain powder added is 25 kg, the amount of 100-mesh waste porcelain powder added is 25 kg, the amount of 60-mesh burned bauxite added is 5 kg, and the amount of 100-mesh burned bauxite added is 5 kg.

[0029] Preparation Example 1.4 Different from Preparation Example 1.2, the amount of 60-mesh waste porcelain powder added in Preparation Example 1.4 is 32 kg, and the amount of 100-mesh waste porcelain powder added is 16 kg.

[0030] Preparation Example 1.5 Different from Preparation Example 1.2, the amount of 60-mesh waste porcelain powder added in Preparation Example 1.5 is 36 kg, and the amount of 100-mesh waste porcelain powder added is 12 kg.

[0031] Preparation Example 1.6 Different from Preparation Example 1.4, the amount of 60-mesh burnt bauxite added in Preparation Example 1.6 is 8 kg, and the amount of 100-mesh burnt bauxite added is 4 kg.

[0032] Preparation Example 1.7 Different from Preparation Example 1.4, the amount of 60-mesh burnt bauxite added in Preparation Example 1.7 is 9 kg, and the amount of 100-mesh burnt bauxite added is 3 kg.

[0033] Preparation Example 1.8 Different from Preparation Example 1.1, the amount of 60-mesh waste porcelain powder added in Preparation Example 1.8 is 12 kg, and the amount of 100-mesh waste porcelain powder added is 36 kg.

[0034] Preparation Example 1.9 Different from Preparation Example 1.1, the amount of 60-mesh burnt bauxite added in Preparation Example 1.9 is 3 kg, and the amount of 100-mesh burnt bauxite added is 9 kg.

[0035] Preparation Example 2 Modified Heavy Calcium Carbonate A modified heavy calcium carbonate is prepared by the following steps: 3960.4 g of heavy calcium carbonate powder was stirred in a water bath at 60° C. with a rotation speed of 600 r / min. 39.6 g of zinc stearate was added to the heavy calcium carbonate powder and mixed for 30 minutes and then cooled to obtain modified heavy calcium carbonate powder.

[0036] Preparation Example 2.2 Different from Preparation Example 2.1, in Preparation Example 2.2, the water bath temperature is 70° C., the rotation speed is 700 r / min, and the mixing time is 50 min.

[0037] Preparation Example 2.3 Different from Preparation Example 2.1, in Preparation Example 2.3, the water bath temperature is 80°C, the rotation speed is 800 r / min, and the mixing time is 70 min.

[0038] Preparation Example 2.4 Different from Preparation Example 2.2, the amount of heavy calcium carbonate added in Preparation Example 2.4 is 3940.9 g, and the amount of zinc stearate added is 59.1 g.

[0039] Preparation Example 2.5 Different from Preparation Example 2.4, the amount of heavy calcium carbonate added in Preparation Example 2.5 is 3921.6 g, and the amount of zinc stearate added is 78.4 g. Example

[0040] Example 1 No heavy calcium carbonate added Example 1.1 A supplement for dry blanks of sanitary ceramics is prepared by the following steps: 5 kg of glaze slurry and 30 kg of blank were added into 0.5 kg of 1% sodium carboxymethyl cellulose solution and mixed to prepare slurry; 60 kg of the clinker powder from Preparation Example 1.1, 5 kg of 100-mesh silicon micropowder and 6 kg of 200-mesh medium-temperature frit powder were added to the prepared slurry and mixed evenly to prepare a supplement for sanitary ceramic dry blanks.

[0041] Example 1.2-1.3 Different from Example 1.1, the raw material ratios in Examples 1.2-1.3 are different, see Table 1 for details.

[0042] Table 1 Ratio of raw materials in Examples 1.1-1.3

[0043] Example 1.4 Different from Example 1.2, the mass fraction of the sodium carboxymethyl cellulose solution in Example 1.4 is 2%.

[0044] Examples 1.5-1.12 Different from Example 1.4, in Examples 1.5-1.12, the clinker powder in Example 1.2 is replaced by an equal amount of clinker powder obtained from Preparation Examples 1.2-1.9, respectively.

[0045] Comparative Example 1 Different from Example 1.1, no clinker powder was added in Comparative Example 1.

[0046] Comparative Example 2 Different from Example 1.1, in Comparative Example 2, no glaze slurry and medium-temperature frit powder were added.

[0047] Comparative Example 3 Different from Example 1.1, in Comparative Example 3, no medium-temperature frit powder was added.

[0048] Example 2 Adding heavy calcium carbonate Example 2.1 A supplement for dry blanks of sanitary ceramics is prepared by the following steps: 10 kg of glaze slurry and 20 kg of blank were added into 0.8 kg of 2% sodium carboxymethyl cellulose solution and mixed to prepare slurry; 50 kg of the clinker powder from Preparation Example 1.6, 10 kg of 100-mesh silicon powder, 3 kg of heavy calcium carbonate and 5 kg of 200-mesh medium-temperature frit powder were mixed to obtain a dry powder; The prepared dry powder is added into the prepared slurry and mixed evenly to obtain a supplement for sanitary ceramic dry blanks.

[0049] Example 2.2 Different from Example 2.1, the amount of heavy calcium carbonate added in Example 2.2 is 4 kg.

[0050] Example 2.3 Different from Example 2.1, the amount of heavy calcium carbonate added in Example 2.3 is 5 kg.

[0051] Example 3 Adding modified heavy calcium carbonate Examples 3.1-3.5 Different from Example 2.2, in Examples 3.1-3.5, the heavy calcium carbonate in Example 2.2 is replaced by an equal amount of modified heavy calcium carbonate obtained from Preparation Examples 2.1-2.5, respectively.

[0052] The sanitary ceramic dry blanks prepared in Examples 1-3 and Comparative Examples 1-3 were filled with fillers respectively into dry blanks with crack-type defects of the same wound surface specifications (wound surface width <8mm, wound surface depth <8mm, and wound surface length <70mm). After the repair was completed, the repaired dry blanks were fired at 1165°C. The following performance test was conducted on the repaired part of the dry blank. The performance test included whether the repaired part was cracked and the firing shrinkage rate. The test data are shown in Table 2.

[0053] 1. Is the repaired part cracked? Observe the repaired part of the fired dry blank to see if it cracks.

[0054] 2. Firing shrinkage The firing shrinkage of the dry blank repair area is tested according to the testing standard QB / T 1548-2015 "Method for determining the linear shrinkage of ceramic blanks".

[0055] Table 2 Performance test data table

[0056] The following describes the present application in detail in conjunction with the data provided in Table 2.

[0057] Combining comparative examples 1-3 and embodiments 1-3, it was found that the repaired dry blanks of the sanitary ceramics prepared by using the sanitary ceramics dry blank fillers prepared by embodiments 1-3 of the present application did not crack, and the firing shrinkage rates were all lower than the firing shrinkage rates of the sanitary ceramics dry blank fillers prepared by comparative examples 1-5, which indicates that the sanitary ceramics dry blank fillers of the present application perform better in repairing dry blank cracks and improving the dry blank quality rate.

[0058] Taking Example 1.1 as a control, the influence of clinker powder was investigated in Comparative Example 1. The results showed that the filler for sanitary ceramic dry blanks prepared in Comparative Example 1 was inferior to that in Example 1.1 in terms of whether the repaired part was cracked and the firing shrinkage rate. This may be because no clinker powder was added in the comparative example, and the filler was completely fired during the secondary firing, resulting in volume shrinkage.

[0059] Taking Example 1.1 as a control, the influence of glaze slurry and medium-temperature frit powder was investigated in Comparative Examples 2-3. The results showed that in Comparative Example 2, no glaze slurry and medium-temperature frit were added, and the prepared sanitary ceramic dry blank filler was worse than that in Example 1.1 in terms of whether the repaired part was cracked and the firing shrinkage rate. In Comparative Example 3, no medium-temperature frit powder was added, and the prepared sanitary ceramic dry blank filler was worse than that in Example 1.1 in terms of whether the repaired part was cracked and the firing shrinkage rate. Moreover, the sanitary ceramic dry blank filler prepared in Comparative Example 2 was worse than that in Comparative Example 3 in terms of whether the repaired part was cracked and the firing shrinkage rate. This may be because the glaze slurry and the medium-temperature frit powder are both high-temperature binders in the filler. During the secondary firing, the glaze slurry and the medium-temperature frit powder melt at high temperature, thereby increasing the viscosity of the filler at high temperature. The viscosity of the medium-temperature frit powder at high temperature is greater than the viscosity of the glaze slurry, which facilitates the bonding of the filler to the cracks of the dry blank and reduces the possibility of cracking or falling off at the repaired part.

[0060] The influence of the raw material ratio was investigated in Examples 1.1-1.3. The results showed that the sanitary ceramic dry blank filler prepared in Example 1.2 performed better in terms of whether the repaired part was cracked and the firing shrinkage rate. This shows that the raw material ratio selected in Example 1.2 is beneficial to improving the performance of the sanitary ceramic dry blank filler in terms of whether the repaired part was cracked and the firing shrinkage rate.

[0061] Taking Example 1.2 as a control, the influence of the mass fraction of the sodium carboxymethyl cellulose solution was investigated in Example 1.4. The results showed that the sanitary ceramic dry blank filler prepared in Example 1.4 performed better in terms of whether the repaired part cracked and the firing shrinkage rate. This shows that the mass fraction of the sodium carboxymethyl cellulose solution selected in Example 1.4 is beneficial to improving the performance of the sanitary ceramic dry blank filler in terms of whether the repaired part cracked and the firing shrinkage rate.

[0062] Taking Example 1.4 as a control, Examples 1.5-1.6 investigated the influence of the ratio of waste porcelain powder and burnt bauxite in the clinker powder. The results showed that the sanitary ceramic dry blank filler prepared in Example 1.5 performed better in terms of whether the repaired part would crack and the firing shrinkage rate. This shows that the ratio of waste porcelain powder and burnt bauxite in the clinker powder selected in Example 1.5 is beneficial to improving the performance of the sanitary ceramic dry blank filler in terms of whether the repaired part would crack and the firing shrinkage rate.

[0063] Taking Example 1.5 as a control, the influence of the ratio of 60-mesh powder particles to 100-mesh powder particles in waste porcelain powder was investigated in Examples 1.7-1.8. The results showed that the sanitary ceramic dry blank filler prepared in Example 1.7 performed better in terms of whether the repaired part was cracked and the firing shrinkage rate. This shows that the ratio of 60-mesh powder particles to 100-mesh powder particles in the waste porcelain powder selected in Example 1.7 is beneficial to improving the performance of the sanitary ceramic dry blank filler in terms of whether the repaired part was cracked and the firing shrinkage rate.

[0064] Taking Example 1.7 as a control, the influence of the ratio of 60-mesh powder particles to 100-mesh powder particles in burned bauxite was investigated in Examples 1.9-1.10. The results showed that the sanitary ceramic dry blank filler prepared in Example 1.9 performed better in terms of whether the repaired part cracked and the firing shrinkage rate. This shows that the ratio of 60-mesh powder particles to 100-mesh powder particles in burned bauxite selected in Example 1.9 is beneficial to improving the performance of the sanitary ceramic dry blank filler in terms of whether the repaired part cracked and the firing shrinkage rate.

[0065] Taking Example 1.4 as a control, in Example 1.11, the 100-mesh powder particles in the waste porcelain powder are excessive, and the prepared sanitary ceramic dry blank filler is inferior to Example 1.4 in terms of whether the repair part is cracked and the firing shrinkage rate. In Example 1.12, the 100-mesh powder particles in the burned bauxite are excessive, and the prepared sanitary ceramic dry blank filler is inferior to Example 1.4 in terms of whether the repair part is cracked and the firing shrinkage rate. This may be because there are fewer large particles in the waste porcelain powder and burned bauxite, and it is difficult to form a stable particle grading with other separated particles in the prepared filler, which reduces the bonding density of the powder particles in the filler and makes it difficult to prevent the firing shrinkage of the filler.

[0066] Taking Example 1.9 as a control, the effect of adding heavy calcium carbonate to the raw materials was investigated in Examples 2.1-2.3. The results showed that the dry blank fillers for sanitary ceramics prepared in Examples 2.1-2.3 were superior to those in Example 1.9 in terms of whether the repaired parts would crack and the firing shrinkage rate. This indicates that adding heavy calcium carbonate to the raw materials is beneficial to improving the performance of the dry blank fillers for sanitary ceramics in terms of whether the repaired parts would crack and the firing shrinkage rate.

[0067] In Examples 2.1-2.3, the effect of the amount of heavy calcium carbonate added to the raw materials was investigated. The results showed that the sanitary ceramic dry blank filler prepared in Example 2.2 performed better in terms of whether the repaired part cracked and the firing shrinkage rate. This shows that the amount of heavy calcium carbonate added selected in Example 2.2 is beneficial to improving the performance of the sanitary ceramic dry blank filler in terms of whether the repaired part cracked and the firing shrinkage rate.

[0068] Using Example 2.2 as a control, the influence of modified heavy calcium carbonate was investigated in Examples 3.1-3.5. The results showed that the dry blank fillers for sanitary ceramics prepared in Examples 3.1-3.5 were superior to those in Example 2.2 in terms of whether the repaired part cracked and the firing shrinkage rate. This indicates that adding modified heavy calcium carbonate to the raw materials is beneficial to improving the performance of the dry blank fillers for sanitary ceramics in terms of whether the repaired part cracked and the firing shrinkage rate.

[0069] In Examples 3.1-3.3, the influence of the preparation process of modified heavy calcium carbonate was investigated. The results showed that the filler for dry blanks of sanitary ceramics prepared in Example 3.2 performed better in terms of whether the repaired part cracked and the firing shrinkage rate. This indicates that the water bath temperature, rotation speed and mixing time for preparing modified heavy calcium carbonate selected in Example 3.2 are beneficial to improving the performance of the filler for dry blanks of sanitary ceramics in terms of whether the repaired part cracked and the firing shrinkage rate.

[0070] Taking Example 3.2 as a control, the influence of the ratio of modified heavy calcium carbonate raw materials was investigated in Examples 3.4-3.5. The results showed that the dry blank filler for sanitary ceramics prepared in Example 3.4 performed better in terms of whether the repaired part cracked and the firing shrinkage rate. This shows that the ratio of zinc stearate and heavy calcium carbonate in the modified heavy calcium carbonate selected in Example 3.4 is beneficial to improving the performance of the dry blank filler for sanitary ceramics in terms of whether the repaired part cracked and the firing shrinkage rate.

[0071] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A supplement for dry ceramic blanks, characterized in that: The invention comprises the following raw materials in parts by weight: 40-60 parts of clinker powder, 5-15 parts of silicon powder, 10-30 parts of green body, 5-15 parts of glaze slurry, 0.5-1 part of 1-2% sodium carboxymethyl cellulose solution by mass, and 4-6 parts of medium temperature frit powder.

2. A supplement for dry ceramic blanks according to claim 1, characterized in that: The particle size of the silicon micropowder is 100±10 mesh, and the particle size of the medium-temperature frit powder is 200±10 mesh.

3. A supplement for dry ceramic blanks according to claim 2, characterized in that: The clinker powder is prepared by mixing waste porcelain powder and burnt bauxite in a weight ratio of (6-10):

2.

4. A supplement for dry ceramic blanks according to claim 3, characterized in that: The waste porcelain powder is prepared by mixing 60±10 mesh waste porcelain powder and 100±10 mesh waste porcelain powder in a weight ratio of (1-3):1, and the burnt bauxite is prepared by mixing 60±10 mesh burnt bauxite and 100±10 mesh burnt bauxite in a weight ratio of (1-3):

1.

5. A supplement for dry ceramic blanks according to claim 4, characterized in that: The raw materials also include 3-5 parts of heavy calcium carbonate powder.

6. A supplement for dry ceramic blanks according to claim 5, characterized in that: The heavy calcium carbonate powder is a modified heavy calcium carbonate powder, which is prepared from zinc stearate and heavy calcium carbonate in a weight ratio of (1-2): 100, and the modified heavy calcium carbonate powder is prepared by the following steps: The heavy calcium carbonate powder is stirred in a water bath at 60-80° C. at a speed of 600-800 r / min, zinc stearate is added to the heavy calcium carbonate powder according to a weight ratio, mixed for 30-70 minutes, and then cooled to obtain a modified heavy calcium carbonate powder.

7. A method for preparing a supplement for dry blanks of sanitary ceramics according to any one of claims 1 to 4, characterized in that: The following steps are involved: Adding glaze slurry and blank into sodium carboxymethyl cellulose solution according to weight parts and mixing evenly to prepare slurry; The clinker powder, silicon powder and medium-temperature frit powder are added into the prepared slurry according to weight proportions and mixed evenly to prepare a supplement for dry blanks of sanitary ceramics.

8. A method for preparing a supplement for dry blanks of sanitary ceramics according to any one of claims 5 to 6, characterized in that: The following steps are involved: Adding glaze slurry and blank into sodium carboxymethyl cellulose solution according to weight parts and mixing evenly to prepare slurry; Mix clinker powder, silicon powder, heavy calcium carbonate and medium-temperature frit powder according to weight to obtain dry powder; The prepared dry powder is added into the prepared slurry and mixed evenly to obtain a supplement for sanitary ceramic dry blanks.

Citation Information

Patent Citations

  • Sanitary ceramics mending material and mending method

    CN106746664A

  • Deep repairing material for fired ceramic body

    CN111646817A

  • Modified ceramic particle wear-resistant repairing agent and preparation method thereof

    CN117363143A

  • Solid for hygiene porcelain glaze and manufacturing method of ceramic ware

    JP2005272231A

  • Sanitary chinaware slip modified with complex plasticizer and Sanitary chinaware body using the same

    KR100869131B1